Father for the first time - development and validation of a questionnaire to assess fathers' experiences of first childbirth (FTFQ) - Premberg Åsa; Taft Charles; Hellström Anna-Lena; Berg Marie (BMC, 2012)
Abstract Background A father's experience of the birth of his first child is important not only for his birth-giving partner but also for the father himself, his relationship with the mother and the newborn. No validated questionnaire assessing first-time fathers' experiences during childbirth is currently available. Hence, the aim of this study was to develop and validate an instrument to assess first-time fathers' experiences of childbirth. Method Domains and items were initially derived from interviews with first-time fathers, and supplemented by a literature search and a focus group interview with midwives. The comprehensibility, comprehension and relevance of the items were evaluated by four paternity research experts and a preliminary questionnaire was pilot tested in eight first-time fathers. A revised questionnaire was completed by 200 first-time fathers (response rate = 81%) Exploratory factor analysis using principal component analysis with varimax rotation was performed and multitrait scaling analysis was used to test scaling assumptions. External validity was assessed by means of known-groups analysis. Results Factor analysis yielded four factors comprising 22 items and accounting 48% of the variance. The domains found were Worry, Information, Emotional support and Acceptance. Multitrait analysis confirmed the convergent and discriminant validity of the domains; however, Cronbach's alpha did not meet conventional reliability standards in two domains. The questionnaire was sensitive to differences between groups of fathers hypothesized to differ on important socio demographic or clinical variables. Conclusions The questionnaire adequately measures important dimensions of first-time fathers' childbirth experience and may be used to assess aspects of fathers' experiences during childbirth. To obtain the FTFQ and permission for its use, please contact the corresponding author.